Necrotizing Enterocolitis: State of the Art in Translating Experimental Research to the Bedside - Ganji, Niloofar; Li, Bo; Lee, Carol; Filler, Rachel; Pierro, Agostino (European Journal of Pediatric Surgery, 2019)
Necrotizing enterocolitis (NEC) is a devastating intestinal disease that continues to have high morbidity and mortality among preterm neonates, despite medical advancements in neonatology and neonatal care. To investigate the pathogenesis of the disease and explore novel form of treatment, a variety of experimental models of NEC have been developed and used by various investigators. These experimental models range from in vitro evaluation of intestinal epithelial cells and intestinal organoids to in vivo models of the disease in neonatal mice, rats, and piglets. Most recently, human-derived intestinal organoids have also been developed and investigated. In this review, we will briefly discuss these experimental models and the contributions that they have made to our understanding of NEC. We will also point to the ischemia/reperfusion (I/R) model of intestinal injury which has been used as an indirect model of NEC by some investigators. Advancements in laboratory research into this devastating disease have continued to expand our knowledge on the pathogenesis and prevention of NEC as well as the effectiveness of therapeutic options for management of this severe disease.
Keywords: necrotizing enterocolitis; organoids; mice; rat; pig